Micro-CT Evaluation of Marginal and Internal Fit of Lithium Disilicate Crowns – Influence of Wax-Up and Manufacturing Technique - Hariri, Soheil; Jamali Ghomi, Ali; Hakimaneh, Seyed Mohammad Reza; Bafandeh , Mohammad Amin; Jahangiri, Maryam; Shayegh, Sayed Shojaedin (Galen Medical Journal, 2024)
Background: Lithium disilicate crowns are widely used in dentistry, with various fabrication methods available. However, there is a research gap in comparing the marginal and internal fit of these crowns produced through different manufacturing techniques. This study aims to evaluate the impact of various manufacturing methods on the marginal and internal fit of lithium disilicate crowns. Materials and Methods: The left maxillary canine’s acrylic tooth was prepared using a high-speed handpiece. Subsequently, the prepared tooth was scanned with a laboratory scanner, and 40 dies were milled with resin. These dies were then divided into four groups (n=10), with lithium disilicate crowns fabricated using different methods for each group: group 1) conventional wax-up method and heat press, group 2) 3D print wax-up method and heat press, group 3) wax-up milling method and heat press, and group 4) CAD/CAM method. The marginal and internal fit of the crowns were assessed using micro-CT by measuring Absolute Marginal Discrepancy (AMD), Marginal Gap (MG), Axial Gap (AG), and Occlusal Gap (OG) at various points. Group comparisons were conducted using one-way ANOVA, while Spearman rank correlation coefficient was used to evaluate variable correlations (α=0.05). Results: ANOVA analysis indicated significant differences among all groups for most examined points except for lingual AMD. In inter-group comparisons, the CAD/CAM method demonstrated superior results in MG buccal, MG lingual, AMD buccal, AG2, AG3, OG1, OG3, and OG4 measurements. The 3D printing method outperformed in AG1 and OG2 comparisons while the milling method excelled in AG4 comparison. Although no significant difference was observed in lingual AMD comparison among groups, the CAD/CAM approach exhibited better average agreement. Overall, the conventional group displayed the weakest performance in terms of adaptation. Conclusions: The study findings suggest that all-digital and semi-digital methods for fabricating lithium disilicate crowns offer better adaptation compared to conventional techniques.